Enforcement of Norms of Women's Representation in The Regional House of Representatives of Pekalongan Regency, Period 2019-2024 - Eni Purwanti; Teti Hadiati (Asian Journal of Law and Humanity, 2022)
Regulations that are more practical in nature regarding women's political rights are stated in the Law of the Republic of Indonesia Number 7 of 2017 concerning General Elections. In this law, all forms of women's representation must meet the 30% figure, both for women's representation in KPU membership, in the management of political parties at the central level, as well as candidates for members of DPR, Provincial DPRD, and Regency/Municipal DPRD. With this reference, it is clear that the Indonesian constitution recognizes women's rights in politics. However, in reality the number of women in the Pekalongan Regency DPRD has not reached 30%. The purpose of this study was to determine the effectiveness of the implementation of Law Number 7 of 2017 concerning General Elections in the DPRD of Pekalongan Regency.